SIFAT FISIKA DAN MEKANIKA PAPAN SEMEN DARI SERAT KULIT BATANG SAGU (Metroxylon Sp) - Peterson, Peterson; Dirhamsyah, M; Nurhaida, Nurhaida (JURNAL HUTAN LESTARI, 2019)
The research aims to examine the physical and mechanical properties of cement board from sago fiber waste (Metroxylon Sp) based on cement size and composition and determine the best ratio of cement and sago fiber (Metroxylon sp) and meet the standards of JIS A 5417: 1992. The study was conducted at the Laboratorium WoodWorkshop, Wood Processing, Wood Technology and PT. Duta Pertiwi Nusantara Pontianak. The method used was an experimental method in a factorial Randomized Complete Design factorial experiment of 2 x 3 with 3 replications and a total of 18 experiments. The factors used in sago fiber length (Factor A) and fiber (Factor B).  The tests include physical properties and mechanical properties with a target density of 1 gr / cm³. The results showed that the average value of the physical properties of the cement board included density 0.9713 gr / cm³ - 1.2246 gr / cm³, moisture content 3.5054% - 3.9448%, water absorption 0.9746 % - 1.1318% and thick Development 0.8649% - 0.9892%. The mean mechanical properties of cement board include MOE 10,564,6646 kg / cm² - 35,475,7865 kg / cm² and MOR 7,5797 kg / cm² - 25,8554 kg / cm². The best research is in treatment (a1b2) with a ratio of cement and fiber (80:20) with a length of sago fiber 2 cm and meets the standards of JIS A 5417: 1992 with the of 23, with a physical property density value of 1.2198 gr / cm³, water content is 3.7401%, water absorption is 0.9944%, and thickness development is 0.9048%. The mechanical properties value of Modulus of Elasticity is 28439.1825 kg / cm² and Modulus of Rupture is 25.8554 kg / cm².Keyword:   Cement Comparison,  Fiber Length, Sago Fiber, Physical and Mechanical Propertie